ANALISIS PENGARUH TEKANAN DAN RASIONALISASI TERHADAP KECURANGAN LAPORAN KEUANGAN - Lilia Arifah; Efrinal Efrinal (AKRUAL : Jurnal Akuntansi dan Keuangan, 2024)
This study aims to determine the effect of pressure and rationalization on financial statement fraud in infrastructure sector BUMN companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The population of this study are state-owned infrastructure companies listed on the Indonesia Stock Exchange for the 2017-2022 period. Samples were taken using purposive sampling technique. The sample used in this study were 6 BUMN companies in the infrastructure sector which were listed on the Indonesia Stock Exchange for the 2017-2022 period, so that the research data analyzed totaled 36. Tests in this study used Multiple Linear Regression Analysis with the Eviews program version 12. The results of the study were partial shows that pressure proxied using Return on Assets (ROA) has a positive and insignificant effect on fraudulent financial statements and rationalization proxied using Change in Auditor has a positive and significant effect on fraudulent financial statements. The results of the study simultaneously show that pressure proxied using Return on Assets (ROA) and rationalization proxied using Change in Auditor have no simultaneous effect on fraudulent financial statements.